PENGATURAN LAYOUT UNTUK OPTIMALISASI KINERJA STREET MAGICIAN - Eduardus Matthew; Irena V.G. Fajarto; Erwin Ardianto Halim S. (Ide dan Dialog Desain Indonesia (Idealog), 2018)
Street magic has similarity with close-up magic, but what’s make it different are the way how the magician perform it and where it happened. Street magicians can almost perform their tricks in anywhere and anytime, even with preparation before it. But usually street magicians perform their tricks in some public spaces, with number of crowd that cannot be calculated. This makes the trick that the magician performed is leaked to people around there, this happened because there’s no safe space or some personalspaces that magician can keep while they’re performing some tricks. The research method are doing some survey (direct & indirect) by doing some interviews to street magicians and observe some street magic videos and then doing review with personal spacestheory. The result shows that the layout of the space can optimize how street magician works. The conclusion is the designed space already appropriate.